2020
DOI: 10.1088/1757-899x/848/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Development of chitosan-hyaluronic acid nanoparticles and study of their physico-chemical properties for targeted delivery of anticancer drugs

Abstract: Nanoparticles from chitosan and hyaluronic acid were obtained using ionotropic gelation technology. The size of the nanoparticles was investigated using electron microscopy and dynamic light scattering. Nanoparticles were obtained of an optimal size of ∼ 100 nm. A physical association method has been developed of encapsulating nanoparticles with doxorubicin, a well-known antitumor drug, and dinitrosyl iron complex (donor of nitric oxide). The surface potential of nanoparticles was determined by dynamic light s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Utilizing confocal and film imaging, Akentieva et al ( 2020) found out that doxorubicin nanoparticles were localized around cells and in the nucleus after using the ionic gelation method to synthesize the drug on a CHA-Np system. In addition, this method could increase the effectiveness of the active ingredient [84].…”
Section: Bladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing confocal and film imaging, Akentieva et al ( 2020) found out that doxorubicin nanoparticles were localized around cells and in the nucleus after using the ionic gelation method to synthesize the drug on a CHA-Np system. In addition, this method could increase the effectiveness of the active ingredient [84].…”
Section: Bladder Cancermentioning
confidence: 99%
“…Therefore, this pH range is the only one where these two polymers can completely ionize and form strong electrostatic interactions [41]. Nanoparticle formulations for doxorubicin entrapment [84], paclitaxel entrapment [69], peptide entrapment [66], curcuminoids entrapment [101], and other nanoparticle formulations require ionic gelation processes.…”
Section: Author Perspectivementioning
confidence: 99%
“…These receptors are present in a great variety of cells, such as macrophages and lymphocytes, but are over-expressed in many types of cancer cells [ 19 ], hence representing a suitable marker for tumor targeting. Therefore, delivery systems that expose HY on the surface can increase intracellular drug accumulation, specifically in CD44 over-expressing cancer cells [ 20 , 21 , 22 ]; this can avoid serious side effects related to cancer therapy. Recently, Lallana et al [ 23 ] realized CS/HY NPs that efficiently deliver a large luciferase-encoding mRNA and a much smaller anti-Luc siRNA into cells overexpressing CD44 receptors.…”
Section: Introductionmentioning
confidence: 99%